Asprosin Can Increase Heterosexual Preference - Serhatlioglu, I.; Oz, Z. D.; Ozdede, M. R.; Ozbeg, G.; Ozgen, A.; Horoz, M. A.; Kelestimur, H. (Wiley, 2022)
[Abstract Not Available]
Keywords: Sexual Incentive Motivation